Prince Edward County, Virginia school closing : a compilation of research studies - Hicks, Terence (Emerald Publishing Limited, 2025)
The Prince Edward County, Virginia School Closing: A Compilation of Research Studies provides readers with a series of qualitative methodology approaches and topics. The collection of studies in this book contributes greatly to the research literature surrounding the school closing and examine topics such as (1) restorative justice, (2) massive resistance, (3) role of memory/racial healing, (4) the Civil Rights Movement, (5) socialization, (6) addressing silence, and (7) the importance of place.